Are social representations of positive ageing really effective? the ageing process through the eyes of elderly - Soares, Célia Cristina Casaca (2014)
In this paper we focused on the experiences of ageing from the perspective of elderly people. Our main aims were to explore their perceptions and representations about the ageing experience and to analyse if their conceptions are closer to positive social representations of active ageing or to ageist social assumptions. Thirty-five females (mean age of 80 years) and seven males (mean age of 73 years) participated in this study, recruited in a network of institutions run by the city council of Setubal. Data collection was conducted with structured interviews and the obtained transcriptions were submitted to qualitative thematic analysis. With this analytic approach it was possible to identify dominant themes in participants discourses. Results show that elderly perceive and represent the process of ageing according to a binary perspective, displaying both positive and negative dimensions. Even if the ageing experience is described according to a positive perspective, it is also anchored on ageist social constructions. Thus the positive social representations of ageing expressed through active ageing discourses are still not fully assimilated and integrated on people s self-perceptions and identities.